2017
DOI: 10.1111/irfi.12124
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy and Informativeness of Reported Earnings: Evidence from the MENA Region

Abstract: This paper documents that informativeness of reported earnings, measured by earnings–return relation, is an increasing function of dividend payout ratio in the Middle East and North Africa region during the period between 2003 and 2014. We argue that higher dividends reduce agency conflicts. Lower agency problems lead firms to disclose information more truthfully, thereby improving credibility of reported earnings. We also show that our results hold for various proxies of dividend policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
2
14
1
Order By: Relevance
“…In conjunction with their findings, this result was revealed that an increase in the discretionary accruals of the firm does not necessarily instigate growth or otherwise in the dividend policy. However, this finding opposed the results of Morghri&Galogahv (2013), (Baatour et al, 2017), Farooq (2018) and Aladwan (2019).…”
Section: Standardized Regression Path Figure 2 Standardized Structurcontrasting
confidence: 69%
See 1 more Smart Citation
“…In conjunction with their findings, this result was revealed that an increase in the discretionary accruals of the firm does not necessarily instigate growth or otherwise in the dividend policy. However, this finding opposed the results of Morghri&Galogahv (2013), (Baatour et al, 2017), Farooq (2018) and Aladwan (2019).…”
Section: Standardized Regression Path Figure 2 Standardized Structurcontrasting
confidence: 69%
“…Similarly, Savov (2006) and Chansarn & Chansarn (2016) have in their separate studies opined that large firms with huge investment tend to disclose more discretionary accrual in their reported earnings. Moreover, various findings indicated that managers attempt to engaged earning manipulation when they realize that the firm may likely not meet the required level of earning to pay the due dividend (see, Morghri & Galogah, 2013) and looking forward to increases the earning to attract more investors (Baatour, Ben Othman & Hussainey, 2017;Farooq, 2018;Aladwan, 2019).…”
Section: Relationships Between Dividend Policy and Real Earning Managmentioning
confidence: 99%
“…For the purpose of this paper, Tobin's Q ( Q ) is used as a measure of firm performance. Consistent with prior literature, we define Tobin's Q as the market value of equity plus book value of assets minus the book value of equity, scaled by book value of assets (Foucault and Frésard, 2012; Singh et al , 2018; Farooq et al , 2018).…”
Section: Datamentioning
confidence: 99%
“…Investors in emerging markets are particularly interested in dividend policies because dividends have significant impact on the market values of firms. Prior literature argues that dividends positively affect the value of firms by reducing the agency problems (La Porta et al, 2000;Farooq et al, 2018). In emerging markets, dividends can substitute for the monitoring roles of stakeholders.…”
Section: Introductionmentioning
confidence: 99%